Body Image dan Social Anxiety pada Remaja Putri Skoliosis Idiopatik: Mengeksplorasi Self-esteem sebagai Mediator: Citra Tubuh dan Kecemasan Sosial pada Remaja Putri Skoliosis Idiopatik: Mengeksplorasi Self-esteem sebagai Mediator - Siti Fatimah Nurhajah; Eny Suwarni; Yuliana Mukti Rahmawati (Faculty of Social Science and Human Ecology, IPB University, 2026)
Adolescent females diagnosed with idiopathic scoliosis frequently encounter body image-related psychological difficulties that induce social anxiety, a condition significantly influenced by their level of self-esteem. The goal of this research is to explore the role of self-esteem in the influence of body image on social anxiety in adolescent females with idiopathic scoliosis. This quantitative study involved 153 adolescent females aged 13–21 years who were diagnosed with idiopathic scoliosis. A mediation design was chosen to investigate the influence of body image on social anxiety, mediated by self-esteem. Purposive sampling was utilized as the sampling technique. The psychological constructs measured included body image, self-esteem, and social anxiety. The findings identified self-esteem as a partial mediator of the relationship between body image and social anxiety among adolescent females with idiopathic scoliosis (β=-0.0996, 95% CI [-0.20, -0.01]). Further analysis showed that negative body image significantly predicted diminished self-esteem, which subsequently predicted elevated levels of social anxiety. Clinical practitioners in the field of psychology are advised to develop psychological interventions that focus on enhancing self-esteem in order to effectively help adolescent females with idiopathic scoliosis reduce social anxiety.